2021
DOI: 10.3389/fpsyt.2021.713386
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Frailty in Patients With Heart Failure: A Systematic Review of the Association Between Frailty and Cognitive Impairment

Abstract: Background/Aim: Pathological processes associated with aging increase the risk of cognitive deficits. Frailty syndrome may significantly accelerate these pathological processes in elderly patients with heart failure. The objective of this review was to better understand the association between frailty syndrome and co-occurring cognitive decline in patients with heart failure.Methods: We conducted a systematic review based on PubMed/MEDLINE, Scopus, EMBASE, and CINAHL as databases. The search followed the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 96 publications
2
12
0
Order By: Relevance
“…Furthermore, our findings were consistent in that cognitive impairment and frailty were related to poor adherence to self‐care behaviours and a higher risk of hospital readmissions (Faulkner et al, 2021; Li et al, 2022; Zhang, Jie, et al, 2022). This might be explained by that these two conditions effect poor self‐care behaviours, such as omitting taking medications, poor physical activities and difficulties in HF symptom management, which can lead to unplanned hospital readmissions due to deterioration of cardiac function (Faulkner et al, 2021). Nonetheless, HF conditions can aggravate cognitive decline and frailty, especially in the older HF population due to the reduced blood supply to the brain and metabolic dysfunction (Naderi et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, our findings were consistent in that cognitive impairment and frailty were related to poor adherence to self‐care behaviours and a higher risk of hospital readmissions (Faulkner et al, 2021; Li et al, 2022; Zhang, Jie, et al, 2022). This might be explained by that these two conditions effect poor self‐care behaviours, such as omitting taking medications, poor physical activities and difficulties in HF symptom management, which can lead to unplanned hospital readmissions due to deterioration of cardiac function (Faulkner et al, 2021). Nonetheless, HF conditions can aggravate cognitive decline and frailty, especially in the older HF population due to the reduced blood supply to the brain and metabolic dysfunction (Naderi et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Namely, HF is prevalent among older people who are likely to have multimorbidity and to experience an age‐related decline in cognitive function (Zhang, Jie, et al, 2022; Zhang, Koirala, et al, 2022). In addition, cerebrovascular haemodynamics changes, including reduced blood supply to the brain, have been postulated to contribute to the cognitive decline in HF patients (Faulkner et al, 2021). Two recent reviews emphasised that regular screening tests and multifactorial approach are required to improve self‐care abilities and clinical outcomes in individuals with HF and cognitive impairment (Faulkner et al, 2021; Zhang, Jie, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Physical frailty refers to the cumulative decline of multiple physiological systems over time, leading to decreased physiological reserves and resistance to stressors in older adults. 5 It is associated with a significant increase in various adverse outcomes, such as falls, 6 dementia 7 and death. 8 Cognitive impairment is a pre-dementia stage in which age-related cognitive decline is insufficiently severe to cause significant impairment in daily functioning.…”
Section: Introductionmentioning
confidence: 99%
“…CAD patients tend to present with reduced gray matter and white matter microstructure compared with controls ( Almeida et al, 2012 ; Vuorinen et al, 2014 ; Anazodo et al, 2015 ); it is also suggested that CAD patients showed cortical thickness in multiple regions of the brain ( Almeida et al, 2012 ; Vuorinen et al, 2014 ). Importantly, reports ( Deckers et al, 2017 ; Elman et al, 2019 ; Faulkner et al, 2021 ; Liang et al, 2021 ) have shown the association between CAD and the risk for cognitive impairment or dementia but very little is known about the association between this link. However, it is suggested that the association between cognitive impairment and CAD may be linked with underlying risk factors (such as hypertension, diabetes mellitus which have been suggested to be linked with cognitive dysfunction), atherosclerosis, and hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%